Kinematic differences between front crawl sprint and distance swimmers at a distance pace - McCabe, C. B.; Sanders, R. H. (Journal of Sports Sciences, 2012)
The purpose of the study was to determine whether there are differences in kinematics between sprint and distance front crawl specialists when swimming at a distance pace using a six beat kick. Seven sprint and eight distance male specialists performed one maximum 400 m swim through a 6.75 m3 calibrated space recorded by six gen-locked cameras. The following variables were calculated: average swim velocity, stroke length, stroke frequency, upper limb and foot displacement, elbow angle, the shoulder and hip roll angle, duration of the stroke phases and time corresponding to particular events within the stroke cycle relative to hand entry. Differences between the groups were assessed by an independent t-test and effect size (d) calculations for each variable. The groups only differed significantly with respect to the average swim velocity, with the distance swimmers maintaining a greater velocity throughout the 400 m. However, effect sizes were moderate for elbow angle range during the pull phase (d = 0.78) and the total hip roll magnitude (d = 0.76). There was little evidence to suggest that sprint and distance swimmers using a six beat kick pattern differ in technique when swimming at a distance pace and therefore coaches should not encourage the development of different techniques between these groups.